Let F = the downstream speed of the water.
<span>Then the boat's upstream speed is: 15 - F </span>
<span>The boat's downstream speed is: 15 + F </span>
<span>Assume both the journeys mentioned take T hours, then using "speed x time = distance" we get: </span>
<span>Downstream journey: (15 + F)T = 140 </span>
<span>Upstream journey: (15 - F)T = 35 </span>
<span>Add the two formulae together: </span>
<span>(15 + F)T + (15 - F)T = 140 + 35 </span>
<span>15T + FT + 15T - FT = 175 </span>
<span>30T = 175 </span>
<span>T = 35/6 </span>
<span>Use one of the equations to find F: </span>
<span>(15 + F)T = 140 </span>
<span>15 + F = 140/T </span>
<span>F = 140/T - 15 </span>
<span>F = 140/(35/6) - 15 </span>
<span>F = 24 - 15 </span>
<span>F = 9 </span>
<span>i.e. the downstream speed of the water is 9 kph </span>
<span>Therefore, the boat's speed downstream is 15 + F = 15 + 9 = 24 kph.
the answer is: *24kph*</span>
Answer:
D. The momentum of Car B is three times as great in magnitude as that of car A.
Explanation:
I majored in Physics
In my opinion it does. The more water the pot holds, the longer you need to wait for it to freeze. Since there is more water, some parts may not be completely frozen. An experiment you can try is to get an ice cube container and a pot. fill both of them and put them in the freezer for the same amount of time. When you take it out, the ice cubes should be frozen leaving the pot with cold water.
Renewable energy
<u>Advantages :-</u>
1. Easily regenerate
2. Boost economic growth
3. Easily available
4. Support environment
5. Low maintenance cost
<u>Disadvantages :-</u>
1. Weather dependency
2. High installation cost
3. Noise caused by wind energy
4. Fluctuation problem (solar)
5. Intermittency issue (wind)
Non-renewable energy
<u>Advantages :-</u>
1. Concentrated energy source
2. Reliable energy source
3. Can be built anywhere
4. No radioactive waste
<u>Disadvantages :-</u>
1. Produces greenhouse gases
2. Contributes to global warming
3. Produces acid rain
4. Harmful to environment when they are burnt
<em>I hope this helps.....</em>
Answer:
![x=\frac{-y+\sqrt{y^2+4rt} }{2r}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-y%2B%5Csqrt%7By%5E2%2B4rt%7D%20%7D%7B2r%7D)
![x=\frac{-y-\sqrt{y^2+4rt} }{2r}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-y-%5Csqrt%7By%5E2%2B4rt%7D%20%7D%7B2r%7D)
Explanation:
![rx+y=\frac{t}{x}\\\\x(rx+y)=(\frac{t}{x})x\\\\rx^2+yx=t\\\\rx^2+yx-t=t-t\\\\rx^2+yx-t=0](https://tex.z-dn.net/?f=rx%2By%3D%5Cfrac%7Bt%7D%7Bx%7D%5C%5C%5C%5Cx%28rx%2By%29%3D%28%5Cfrac%7Bt%7D%7Bx%7D%29x%5C%5C%5C%5Crx%5E2%2Byx%3Dt%5C%5C%5C%5Crx%5E2%2Byx-t%3Dt-t%5C%5C%5C%5Crx%5E2%2Byx-t%3D0)
Solve using the quadratic formula.
![x=\frac{-y+\sqrt{y^2+4rt} }{2r}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-y%2B%5Csqrt%7By%5E2%2B4rt%7D%20%7D%7B2r%7D)
![x=\frac{-y-\sqrt{y^2+4rt} }{2r}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-y-%5Csqrt%7By%5E2%2B4rt%7D%20%7D%7B2r%7D)